The Effect of Accounting Information Systems And Internal Audits on Internal Control at PT. Sierra Mandiri Distribusindo - Putri Wahyuni; Muammar Rinaldi; Anton Eka Saputra (Institute of Computer Science (IOCS), 2022)
This research aims to determine the effect of Accounting Information Systems on Internal Control at PT. Sierra Mandiri Distribusindo, knowing the effect of Internal Audit on Internal Control at PT. Sierra Mandiri Distribusindo, knowing the effect of the Accounting Information System and Internal Audit on Internal Control at PT. Sierra Mandiri Distribusindo. The population in this research were employees at PT. Sierra Mandiri Distribusindo. Samples taken were from 38 respondents using the saturated sampling method. Data was collected through a questionnaire. The results showed that the Accounting Information System and Internal Audit partially had a positive and significant effect on Internal Control at PT.Serra Mandiri Distribusindo. The results showed that the Accounting and Internal Audit Information System simultaneously had a positive and significant effect on Internal Control at PT.Serra Mandiri Distribusindo. The results of this research are supported by the value of R square (R2) which means that the Accounting and Internal Audit Information System influences Internal Control. while the rest are explained by other variables not examined in this research, such as information technology and employee performance.